Beyond the management view: A ressource-centered socio-economic perspective - Manfred Moldaschl; Dirk Fischer (Management Revue, 2004)
This essay addresses the role of transaction cost economics (TCE) in advancing the resource-based view. In particular, it is argued that TCE has the potential to remedy a number of weak spots in the RBV, such as the absence of attention in the RBV to the interaction between value creation and value appropriation. This and other weak spots in the RBV stem from not taking account of transaction costs to a sufficient extent. Integrating TCE with the RBV adds new insight into the analysis of sustained competitive advantage.
Keywords: 650; the resource-based view; transaction cost economics; sustained competitive advantage; Ressourcenorientierter Ansatz